Factors Impacting University Instructors’ and Students’ Perceptions of Course Effectiveness and Technology Integration in the Age of Web 2.0 - Venkatesh, Vivek; Rabah, Jihan; Fusaro, Magda; Couture, Annie; Varela, Wynnpaul; Alexander, Kristopher (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2016)
We are witnessing the integration of increasingly sophisticated information and communication technologies (ICTs) in higher education settings. Understanding learners’ and instructors’ perceptions of their proficiency and use of ICTs is critical to the success of their integration in universities. Using a theoretical framework grounded in technology integration and educational psychology, survey data were collected from students and instructors spanning 12 Quebec universities. Results show that, for instructors, the efficacy of ICT use, and constructivist, interactive forms of teaching most strongly predict a positive perception of the classroom learning experience. Meanwhile, for students, stimulating lectures are the chief predictors of their learning appreciation. Directions for future research are discussed in light of the results of this study.